2014
DOI: 10.1364/ol.39.001949
|View full text |Cite
|
Sign up to set email alerts
|

Heterodyne displacement interferometer, insensitive for input polarization

Abstract: Periodic nonlinearity (PNL) in displacement interferometers is a systematic error source that limits measurement accuracy. The PNL of coaxial heterodyne interferometers is highly influenced by the polarization state and orientation of the source frequencies. In this Letter, we investigate this error source and discuss two interferometer designs, designed at TU Delft, that showed very low levels of PNL when subjected to any polarization state and/or polarization orientation. In the experiments, quarter-wave pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The interaction of the periodic laser interferometer non-linearities with the probe under calibration was further studied by Köning [27] and Sacconi [28]. Also, dedicated laser interferometers been designed that exhibit hardly or no detectable non-linearities [29,30], or systems were designed to compensate these [31][32][33][34]. In that case these may compete for the noise-characteristics with the systems based on Fabry-Pérot interferometers as discussed in the next section.…”
Section: Systems Based On Displacement Laser Interferometermentioning
confidence: 99%
“…The interaction of the periodic laser interferometer non-linearities with the probe under calibration was further studied by Köning [27] and Sacconi [28]. Also, dedicated laser interferometers been designed that exhibit hardly or no detectable non-linearities [29,30], or systems were designed to compensate these [31][32][33][34]. In that case these may compete for the noise-characteristics with the systems based on Fabry-Pérot interferometers as discussed in the next section.…”
Section: Systems Based On Displacement Laser Interferometermentioning
confidence: 99%
“…Frequency leakage (and thereby PNL) can be prevented by spatially separating the source frequencies throughout the interferometer system until detection [11][12][13][14][15][16][17][18]. The main advantage of separated source frequency delivery is that it can take place either free-space as well as via optical fibers, offering a reconfigurable means of optical transport at minimum space consumption and enabling complete fiber-coupled heterodyne displacement interferometers [see Fig.…”
mentioning
confidence: 99%
“…The research discussed in this Letter is based upon previous research on the "Delft interferometer" [14][15][16], which reported on its measurement performance when fed with two fiber-delivered source frequencies (using polarization maintaining single-mode fibers) [15]. It did not, however, extensively analyze time variant influences of external disturbances acting on the fiber delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The heterodyne interferometer uses the dual-frequency beam with a certain frequency difference Δf as a carrier signal. With the rapid development of electronic phase measurement technology, the resolution of the displacement measurement of the heterodyne interferometry has reached subnanometer [37].…”
Section: List Of Figuresmentioning
confidence: 99%